Human Life (Before Birth - Dye, Frank J. (Frank John), 1942- (Milton : Chapman and Hall/CRC, 2019)
This textbook presents essential and accessible information about human embryology including practical information on human health issues and recent advances in human reproductive technology. Starting with biological basics of cell anatomy and fertilization, the author moves through the development of specific organs and systems, before addressing social issues associated with embryology. Each chapter includes specific objectives, general background, study questions, and questions to inspire critical thinking. Human Life Before Birth also contains two appendices and a full glossary of terms covered in the text. Clinicians and researchers in this field will find this volume indispensable. Key selling features: Explores all the developmental and embryological events that occur in human emryonic and fetal life Reviews basic cell biology, genetics, and reproduction focusing entirely on humans Summarizes the development of various anatomical systems Examines common birth defects and sexually transmitted diseases including emerging concerns such as Zika Documents assisted fertilization technologies and various cultural aspects of reproduction
Blastocyst (initiation of cell differentiation)Two-layered embryonic disc; Gastrulation and the three-layered embryonic disc; Neurulation; Neural tube; Neural crest; Embryonic induction; The changing mesoderm; Somitic, intermediate, and lateral mesoderm; Cardiogenic mesoderm; From layers to tubes: The fourth week; Becoming a recognizable human: Weeks 5-8; Cell movements; Artificial embryos; Study questions; Critical thinking; 9. The fetal period; Developmental changes; Sex determination; Growth; Subdivisions of the fetal period; Early fetal stage or "the fetus goes to sleep" (9-18 weeks)
Description based upon print version of record.
Middle fetal stage or "an awkward stage" (19-28 weeks)
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Life Sciences / Biology / Developmental Biology; MEDICAL / Gynecology & Obstetrics; MEDICAL / Reproductive Medicine & Technology; Embryology, Human; Fetus -- Growth; Fetus -- Physiology